A Cross‐Sectional Test of Sign Creation by Children in the Gesture and Vocal Modalities. Issue 6 (12th May 2021) - Lister, Casey J.; Burtenshaw, Tiarn; Walker, Bradley; Ohan, Jeneva L.; Fay, Nicolas
Abstract : Naturalistic studies show that children can create language‐like communication systems in the absence of conventional language. However, experimental evidence is mixed. We address this discrepancy using an experimental paradigm that simulates naturalistic sign creation. Specifically, we tested if a sample of 6‐ to 12‐year‐old children (52 girls and 56 boys drawn from an urban, predominantly white population in Western Australia) can comprehend and create novel gestural and vocal signs. Experiment 1 tested children's ability to comprehend novel signs. Experiment 2 tested children's ability to create novel signs. Results show that children can comprehend and create gestural and vocal signs, that communication is more successful in the gesture modality, and that older children outperform younger children.